A systematic review of pseudarthrosis and reoperation rates in minimally invasive adult spinal deformity correction - Sandhya Kalavacherla; Lauren E. Stone; Carson P. McCann; Megana Saripella; Martin H. Pham (World Neurosurgery: X, 2024)
Background/objective: The recent development of minimally invasive surgical techniques (MIS) has made possible the correction of adult spinal deformity (ASD) with less blood loss and shorter hospital stays. However, minimally invasive placement of pedicle screws at the proximal level of the construct can increase pseudarthrosis risk, leading to implant failure, kyphosis, and reoperations. We aggregate existing literature to describe pseudarthrosis rates at the proximal thoracic or thoracolumbar junction in MIS and subsequent reoperation rates. Methods: After a three-tied search strategy in PubMed, we identified 9 articles for study inclusion, describing outcomes from MIS correction of ASD, pseudarthrosis as complication, and surgery on 4+ levels. Baseline patient characteristics and combined rates of pseudarthrosis and reoperation were calculated. Results: A total of 482 patients were studied with an average [range] age of 65.5 [60.4,72], 6.3 [4.4,11] levels fused per patient, follow-up time of 28.3 [12,39] months, and 64.8% females. Pseudarthrosis was reported in 28 of 482 pooled patients (5.8%) of which 15 of 374 pooled patients (4.0%) ultimately underwent a reoperation for pseudarthrosis. Post-operative characteristics included an estimated blood loss (EBL) of 527.1 [241,1466] mL, operating time of 297.9 [183,475] minutes, and length of stay of 7.7 [5,10] days. Among the papers comparing MIS to open surgery, all reported a significantly lower EBL in patients treated with MIS. Conclusion: This analysis demonstrate a measurable pseudarthrosis risk when using MIS to treat ASD, overwhelming requiring reoperation. The benefits of MIS must be considered against the drawbacks of pseudarthrosis when determining ASD management.